Stimuli-sensitive thiolated hyaluronic acid based nanofibers: synthesis, preclinical safety and in vitro anti-HIV activity. (November 2016) - Agrahari, Vivek; Meng, Jianing; Ezoulin, Miezan JM; Youm, Ibrahima; Dim, Daniel C; Molteni, Agostino; Hung, Wei-Ting; Christenson, Lane K; Youan, Bi-Botti C
Aim: To develop a seminal enzyme bioresponsive, mucoadhesive nanofibers (NFs) as safe and effective nanocarriers for the prevention of HIV vaginal transmission.Methods: A novel thiolated hyaluronic acid (HA-SH) polymer was synthesized to fabricate tenofovir (TFV)-loaded electrospun NFs (HA-SH-NFs) and characterized in vitro/in vivo .Results: A triggered drug release (87% w/w) from the engineered HA-SH-NFs (mean diameter ∼75 nm) occured within 1 h under the influence of seminal hyaluronidase enzyme. HA-SH-NFs were noncytotoxic, induced no damage on the C57BL/6 mice genital-tract and other organs. No significant CD45 cell-infiltration and changes in cytokines level in cervicovaginal tissues were observed. HA-SH-NFs significantly enhanced both TFV retention and bioavailability in vaginal tissue compared with the 1% TFV-gel. The anti-HIV activity of TFV (on pseudotyped virus followed by luciferase assay) was not adversely affected by the electrospinning process.Conclusion: HA-SH-NFs developed in this study could potentially serve as a safe nanotemplate for topical intravaginal delivery of HIV/AIDS microbicides.